2016
DOI: 10.1097/htr.0000000000000217
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Features on Continuous Electroencephalography Predict Rehabilitation Outcomes After Severe Traumatic Brain Injury

Abstract: The presence of sleep features in the acute period after TBI indicates earlier participation in rehabilitative therapies and a better functional recovery. By contrast, status epilepticus, other ictal activity, or absent sleep architecture may portend a worse prognosis. Whether sleep elements detected by EEG predict long-term prognosis remains to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 32 publications
1
38
1
Order By: Relevance
“…Previous studies revealed that post-TBI seizures in humans are associated with elevated intracranial pressure, longer-lasting cerebral metabolic distress related to an increase in the lactate/ pyruvate ratio, hippocampal atrophy, increased mortality, and the development of post-traumatic epilepsy. 2,3,5,37 These studies concluded that post-TBI seizures, although largely non-convulsive, are therapeutic targets for improving post-TBI outcome. In rats, a 2.8-atm fluid-percussion impact at the end of isoflurane anesthesia into a 5-mm-diameter craniotomy with the center coordinate 4 mm posterior to bregma and 2.5 mm lateral to midline results in an approximately 20-mm 2 cortical lesion with an epicenter in the left auditory cortex.…”
Section: Status Epilepticus After Tbi 1903mentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies revealed that post-TBI seizures in humans are associated with elevated intracranial pressure, longer-lasting cerebral metabolic distress related to an increase in the lactate/ pyruvate ratio, hippocampal atrophy, increased mortality, and the development of post-traumatic epilepsy. 2,3,5,37 These studies concluded that post-TBI seizures, although largely non-convulsive, are therapeutic targets for improving post-TBI outcome. In rats, a 2.8-atm fluid-percussion impact at the end of isoflurane anesthesia into a 5-mm-diameter craniotomy with the center coordinate 4 mm posterior to bregma and 2.5 mm lateral to midline results in an approximately 20-mm 2 cortical lesion with an epicenter in the left auditory cortex.…”
Section: Status Epilepticus After Tbi 1903mentioning
confidence: 99%
“…S tudies in humans monitored by electroencephalography in the intensive care unit show that approximately 20-30% of patients with severe traumatic brain injury (TBI) have nonconvulsive seizures or nonconvulsive status epilepticus (NCSE), [1][2][3][4][5] and 33% present in the first 3 days after injury. 6 Seizure occurrence exhibits a bimodal distribution, peaking at 29 h and 140 h postinjury.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When interpreting the EEG of a comatose patient, clinicians do not only rely on previously seen coma‐EEG but also evoke their longtime acquired experience with EEG recordings in other conditions. In the context of prognostication after CA, clinicians might for instance recognize the presence of typical patterns of nonrapid eye movement (NREM) sleep, which can be suggestive of a favorable outcome for patients in the Intensive Care Unit (Murray, Boylan, Ryan, & Connolly, ; Sandsmark et al, ). We wanted to determine whether the performance of the network could be improved by teaching it to recognize elements of sleep stage NREM‐2 (sleep‐spindles or K‐complexes) or NREM 3 (rhythmic delta activity).…”
Section: Discussionmentioning
confidence: 99%
“…48 Some, if not all, of these processes may be related to the healing and recovery process after brain injury. 49 Studies in comatose patients with continuous EEG monitoring have demonstrated that the presence of sleep architecture is associated with a good outcome, 50 yet SWS quantification and association with recovery has not yet been performed in a human TBI series.…”
Section: Tbi Effects On Clinical Sleep Parametersmentioning
confidence: 99%